PENGARUH PEMAHAMAN PENGENAAN PAJAK PERTAMBAHAN NILAI (PPN) TERHADAP DAYA BELI KONSUMEN KENDARAAN BERMOTOR DI WILAYAH JAWA TIMUR - Laurina Trisnaning Putri; Laurina Trisnaning Putri (UIN Mahmud Yunus Batusangkar, 2022)
This research and analysis has the main objective, namely to see the effect of the imposition of VAT on the purchasing power of motorized vehicle consumers in the East Java region. The author uses a quantitative descriptive approach and the population of this study is all people in the East Java region who already have motorized vehicles and are 17 years and over. The data collection technique used a questionnaire and the data analysis used was a simple linear regression analysis, therefore it can be seen that there is a VAT on the purchasing power of motorized vehicle consumers in the East Java region. This is evidenced by the correlation coefficient between Value Added Tax and Purchasing Power of 0.398, which means a positive correlation and has a very strong relationship. This means that if prices rise, consumers' purchasing power will decrease resulting in taxes imposed in the form of VAT will also decrease.